PENGARUH PENERAPAN MANAJEMEN RESIKO BISNIS DALAM BISCOTTI CAKERY & COFFEE - Cristina Cristina; Cindy Cindy; Dennys Ng; Jeffrey Andelson; Thalia Wang (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Café is one of the popular businesses among the public because it offers a comfortable place to relax while enjoying drinks and snacks. However, like other businesses, cafes also face risks that need to be managed well to operate efficiently and generate optimal profits. One of the risks often faced by cafes is operational risk, such as stock loss, delayed orders, and product quality issues. These risks can lead to financial losses and damage the cafe's reputation if not handled properly. The purpose of this research is to analyze the implementation of business risk management at Biscotti Cakery and Coffee. Data will be collected through in-depth interviews with cafe owners, managers, and employees involved in risk management. Qualitative data will be analyzed using a thematic analysis approach. To ensure the validity of the data, the researcher will use data source triangulation and method triangulation. This will help ensure that the research findings are reliable and valid. The suggestions you've given regarding Biscotti Cakery are very good for improving service and managing risks. Having a strong leader and providing good service to customers are indeed key to success in the food and beverage business. Adding a warning if there is a mistake and offering attractive promotions can also increase customer interest. The use of digital promotions and expanding the menu are also good steps to reach more customers.